Immunohistochemistry markers for lesions preceding HPV-induced cervical cancer: the role of tumoral suppression P16INK4A protein P16INK4A - Eleutério Junior , José; Giraldo, Paulo C (Brazilian Journal of Sexually Transmitted Diseases, 2006)
The HPV and cervical squamous intra-epithelial neoplasia relation is established. The mechanisms used by the virus which causes the transformationof the squamous intra-epithelial are associated to the E6 and E7 HPV genes The E7 gene has an important role inducing the host cell changes which are related to the retinoblastoma protein and E2F transcription factor. Whenthe phenomenon induced by the E7 occurs, there is the expression of the p16INK4aprotein which can be detected by immunohistochemistry. Recentstudies have shown the importance of the use of the p16INK4aas a marker for cellular transformation induced by HPV and its clinical use in practice,mainly helping in the diagnosis of high grade squamous intra-epithelial lesions in biopsies. This revision intends to provide to the reader an update tothe understanding of how cellular markers can contribute to improve the differential diagnosis of the squamous intra-epithelial neoplasia and its prog-nosis.